Collins Easy Learning Italian Grammar - Collins Dictionaries (London, United Kingdom Collins, 2006)
Collins Easy Learning Italian Grammar provides beginners and intermediate learners with a clear and straightforward guide to Italian grammar. The book covers all regular verb forms and conjugations, as well as the most common tenses of irregular verbs. Hundreds of real Italian examples illustrate grammatical points, aiding in comprehension and application. The attractively presented layout ensures that learners can quickly find the information they need, making it an ideal companion for study at school, work, or home.
Collins Easy Learning Italian Grammar is part of the renowned Collins Easy Learning series, designed to provide clear and accessible grammar guidance for learners of Italian. This edition offers a user-friendly layout with key grammatical points highlighted for reinforcement, making it suitable for self-study, classroom use, or revision purposes. The book includes a comprehensive glossary of grammatical terms and an index of over a thousand verbs cross-referenced to their conjugation models. Its practical approach and real-life examples make it an essential resource for anyone aiming to improve their Italian language skills.
Keywords: Collins Easy Learning Italian Grammar